MiR‐2861 as novel HDAC5 inhibitor in CHO cells enhances productivity while maintaining product quality. Issue 10 (30th June 2015) - Fischer, Simon; Paul, Albert Jesuran; Wagner, Andreas; Mathias, Sven; Geiss, Melanie; Schandock, Franziska; Domnowski, Martin; Zimmermann, Jörg; Handrick, René; Hesse, Friedemann; Otte, Kerstin
ABSTRACT Histone deacetylase (HDAC) inhibitors have been exploited for years to improve recombinant protein expression in mammalian production cells. However, global HDAC inhibition is associated with negative effects on various cellular processes. microRNAs (miRNAs) have been shown to regulate gene expression in almost all eukaryotic cell types by controlling entire cellular pathways. Since miRNAs recently have gained much attention as next‐generation cell engineering tool to improve Chinese hamster ovary (CHO) cell factories, we were interested if miRNAs are able to specifically repress HDAC expression in CHO cells to circumvent limitations of unspecific HDAC inhibition. We discovered a novel miRNA in CHO cells, miR‐2861, which was shown to enhance productivity in various recombinant CHO cell lines. Furthermore, we demonstrate that miR‐2861 might post‐transcriptionally regulate HDAC5 in CHO cells. Intriguingly, siRNA‐mediated HDAC5 suppression could be demonstrated to phenocopy pro‐productive effects of miR‐2861 in CHO cells. This supports the notion that miRNA‐induced inhibition of HDAC5 may contribute to productivity enhancing effects of miR‐2861. Furthermore, since product quality is fundamental to safety and functionality of biologics, we examined the effect of HDAC inhibition on critical product quality attributes. In contrast to unspecific HDAC inhibition using VPA, enforced expression of miR‐2861 did not negatively influence antibody aggregation or N‐glycosylation. Our findings highlight the superiority of miRNA‐mediated inhibition of specific HDACs and present miR‐2861 as novel cell engineering tool for improving CHO manufacturing cells. Biotechnol. Bioeng. 2015;112: 2142–2153. © 2015 Wiley Periodicals, Inc.